Institutional defence in a total institution: the case of an internment centre for under-age delinquents - Neves, Tiago (2007)
This essay is based on ethnographic work carried out over about a year in an institution for the internment and re-education of under-age delinquents - the Centro Educativo de Santo António (St. Anthony's Educational Centre). The essay analyses and discusses the linkages between institutional defence, identified as a core process in the day-to-day organization of the Education Centre, and the re-education process, which is an integral part of the institution's objectives. This idea of institutional defence is rooted in Adolphe Prins' social defence project, in Weber's concept of bureaucracy and in the logic of managerialism, which is important currently not only in the sphere of juvenile law-making as in the educational sphere.